2017
DOI: 10.1002/pits.21989
|View full text |Cite
|
Sign up to set email alerts
|

The Student-Teacher Relationship Quality of Abused Children

Abstract: Considering the association between children’s quality of relationships with teachers and their academic adjustment, information pertaining to how abused children are functioning in their relationships with teachers could be useful in promoting their academic success— yet there has been limited research in this area. The purpose of this study was to use cluster analyses to explore within-group differences in relational schemas and quality of student-teacher relationships for 70 abused children. Two clusters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Sharing negative relationships with teachers can also hamper students' engagement in class (Roorda et al, 2011). It was also shown that a negative relationship decreases closeness and increases conflict (Armstrong et al, 2017;Pianta et al, 1995).…”
Section: Relationshipsmentioning
confidence: 99%
“…Sharing negative relationships with teachers can also hamper students' engagement in class (Roorda et al, 2011). It was also shown that a negative relationship decreases closeness and increases conflict (Armstrong et al, 2017;Pianta et al, 1995).…”
Section: Relationshipsmentioning
confidence: 99%
“…Sharing negative relationships with teachers can also hamper students' engagement in class (Roorda et al, 2011). It was also shown that a negative relationship decreases closeness and increases conflict (Armstrong et al, 2017;Pianta et al, 1995).…”
Section: Relationshipsmentioning
confidence: 99%